Investigation of Morphological, Optical, and Dielectric Properties of RF Sputtered WOx Thin Films for Optoelectronic Applications - Mahjabin S.; Haque M.M.; Sobayel K.; Selvanathan V.; Jamal M.S.; Bashar M.S.; Sultana M.; Hossain M.I.; Shahiduzzaman M.; Algethami M.; Alharthi S.S.; Amin N.; et al. (MDPI, 2023)
Tungsten oxide (WOx) thin films were synthesized through the RF magnetron sputtering method by varying the sputtering power from 30 W to 80 W. Different investigations have been conducted to evaluate the variation in different morphological, optical, and dielectric properties with the sputtering power and prove the possibility of using WOx in optoelectronic applications. An Energy Dispersive X-ray (EDX), stylus profilometer, and atomic force microscope (AFM) have been used to investigate the dependency of morphological properties on sputtering power. Transmittance, absorbance, and reflectance of the films, investigated by Ultraviolet-Visible (UV-Vis) spectroscopy, have allowed for further determination of some necessary parameters, such as absorption coefficient, penetration depth, optical band energy gap, refractive index, extinction coefficient, dielectric parameters, a few types of loss parameters, etc. Variations in these parameters with the incident light spectrum have been closely analyzed. Some important parameters such as transmittance (above 80%), optical band energy gap (~3.7 eV), and refractive index (~2) ensure that as-grown WOx films can be used in some optoelectronic applications, mainly in photovoltaic research. Furthermore, strong dependencies of all evaluated parameters on the sputtering power were found, which are to be of great use for developing the films with the required properties. 2022 by the authors.